Pemberian Berbagai Dosis Pupuk Organik Mashitam dan Pupuk NPK 25:7:7 pada Tanaman Kubis (Brassica oleracea var. Capitata L.) - Arnis En Yulia; Husna Yetti (Universitas Riau, 2008)
This research aimed toknow influence of interaction of mashitam organic fertilizer dosage and NPK 25:7:7 to the productivity of cabbage (Brassica oleracea var. Capitata L.). the Treatments were arranged in a factorial 3x3 of Completely Randomized Design with 3 replications. The first factor was mashitam organic fertilizerdosage of 3 levels namely 250, 500, and 750 kg/ha and the second factor was NPK 25:7:7 dosage of 3 levels namely 0, 70, and 140 kg/ha. Parameters observed were cabbage crop forming time, harvest age, crop diameter and fresh weight of cabbage crop. Application of 500 kg/ha mashitam organic fertilizer and 140 kg/ha NPK 25:7:7 provided the highest result.